Analysis and description of sensory environmental enrichment in the behavior of domestic cats (Felis catus) from shelters - Cumbe-Nacipucha, Patricia Katiusca; Valencia-Kanut, Erik Sandor; Yupa Zumba, Ángel Fernando (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
The objective of this study was to analyze and describe the impact of auditory and visual sensory environmental enrichment on shelter cats. To this end, behavior was observed in three phases. In each phase, the cats were exposed to different types of stimuli, including music and moving technological objects. Behaviors were grouped into the categories of affiliative, agonistic, calm, exploratory, locomotion, and maintenance. In total, 23 behaviors were observed across the different categories. Descriptive and inferential statistical analyses were performed using the Kruskal-Wallis test, the Mann-Whitney U test, and principal component analysis. Higher rates of allogrooming, lying down, interaction with objects, walking, grooming, and trotting were found, suggesting that sensory environmental enrichment is an effective alternative for improving the well-being and coexistence of cats in the shelter.